A Study of Transmission Control Method for Distributed Parameters Measurement in Large Factories and Storehouses - Shujing Su; Min Yi; Wei Ji; Qing He; Xiufeng Xie (Journal of Electrical and Computer Engineering)
For the characteristics of parameters dispersion in large factories, storehouses, and other applications, a distributed parameter measurement system is designed that is based on the ring network. The structure of the system and the circuit design of the master-slave node are described briefly. The basic protocol architecture about transmission communication is introduced, and then this paper comes up with two kinds of distributed transmission control methods. Finally, the reliability, extendibility, and control characteristic of these two methods are tested through a series of experiments. Moreover, the measurement results are compared and discussed.